Mechanisms of fibrosis formation following glaucoma filtration surgery - Wei-Dao Zhang; Xin Li; Jun Feng; Jie Chen (International Journal of Ophthalmology, 2025)
Glaucoma filtration surgery (GFS) stands as the most effective intervention for reducing intraocular pressure, a critical component in glaucoma management. Despite its pivotal role, the scarring of the filtration bleb remains the primary impediment to successful GFS outcomes. Perioperative utilization of antimitotics, while frontline in combating fibrosis and modulating the wound healing process, carries the risk of vision-threatening complications. Given the complexity of the wound healing cascade and the potential insufficiency of targeting a single molecule, there is an imperative to expand therapeutic modalities through combination therapies. This review offers a comprehensive elucidation of the fibrogenesis post-GFS, a synthesis unprecedented in the available literature, and aims to inform the broadening of therapeutic strategies for GFS.